TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP JUAL-BELI SEPATU MENGGUNAKAN SISTEM RAFFLE (UNDIAN) (Studi Kasus Event Bandung Sneakers Season 2.0) - Fachry Fachrurrozy; Asep Mustafa Kamal; Aan Radiana (Al-Muamalat: Jurnal Ekonomi Syariah, 2020)
Buying and selling with a raffle system is a buying and selling process that uses a lottery to determine the potential buyers who are entitled to buy the items they selected. One of the events that have raffle mechanism is Bandung Sneakers Season 2.0 (BSS 2.0) event. The purpose of this research is to study the mechanism, advantages and disadvantages, and the process of selling and buying of shoes with the raffle system of BSS 2.0 according to Islamic economic law. The method used in this research is descriptive method that is intended to provide a description of the phenomenon or object of research. The results of this study prove that there are three types of raffle mechanisms at BSS 2.0 event. The advantages that can be obtained in the raffle system are minimizing charting, saving time and conducive, while the disadvantages that can be obtained are tickets that must be purchased in greater quantities, and requiring potential shoe buyers to buy unneeded products. Raffle mechanism with tickets obtained for free is a permitted transaction, whereas raffle with tickets obtained by buying sponsor products or buying it directly is a unallowed transaction because there is an element of gambling.